2015
DOI: 10.1016/j.autrev.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells in vitiligo: Implications for pathogenesis and therapeutics

Abstract: Vitiligo is a hypomelanotic autoimmune skin disease arising from a breakdown in immunological self-tolerance, which leads to aberrant immune responses against melanocytes.Regulatory T cells (Tregs) are crucial to the development of self-tolerance and so are major foci in the study of autoimmune pathogenesis of vitiligo. This review will summarise recent findings concerning the role of Tregs in the pathogenesis of vitiligo. In addition, as antigen-specific Tregs are a potential route for the reinstatement of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(132 citation statements)
references
References 110 publications
3
92
0
17
Order By: Relevance
“…Recently, the use of Tregs for therapeutic purpose in the treatment of autoimmune diseases is gaining importance. In a review article, Dwivedi et al, [17] have discussed the therapeutic potential of Tregs in treatment of vitiligo (an autoimmune skin depigmenting disorder) including the use of probiotics for the induction of Tregs, in addition to adoptive transfer therapy using Tregs, especially heatshock protein-specific Tregs. Other markers expressed by Treg include glucocorticoid-induced tumour necrosis factor receptor-related protein (GITR; also known as TNFRSF18, and CD357) and lymphocyte activation gene-3 (LAG-3) [29] and CD127 [30].…”
Section: Regulatory T Cells (Tregs) and Autoimmunitymentioning
confidence: 99%
“…Recently, the use of Tregs for therapeutic purpose in the treatment of autoimmune diseases is gaining importance. In a review article, Dwivedi et al, [17] have discussed the therapeutic potential of Tregs in treatment of vitiligo (an autoimmune skin depigmenting disorder) including the use of probiotics for the induction of Tregs, in addition to adoptive transfer therapy using Tregs, especially heatshock protein-specific Tregs. Other markers expressed by Treg include glucocorticoid-induced tumour necrosis factor receptor-related protein (GITR; also known as TNFRSF18, and CD357) and lymphocyte activation gene-3 (LAG-3) [29] and CD127 [30].…”
Section: Regulatory T Cells (Tregs) and Autoimmunitymentioning
confidence: 99%
“…In summary, autoimmunity has an important role to play in vitiligo development with key contributions from anti-melanocyte autoreactive cytotoxic T cells [19], T helper 17 cells [74,75], and Treg cells [77][78][79].…”
Section: Resultsmentioning
confidence: 99%
“…Natural Treg cells play a key role in maintaining peripheral tolerance through the active suppression of self-reactive T cell activation and expansion [76], thereby preventing the development of the autoimmune responses. To date, several studies have indicated perturbations in Treg cell numbers and/or function in vitiligo patients [67,[77][78][79]. Such alterations might lead to the reported higher levels and activation of cytotoxic T cells in individuals with the disease [67,77].…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…Several reports including ours have suggested a decreased CD4 + ⁄CD8 + ratio in vitiligo patients, indicating the prevalence of CD8 + cells in patients [5658]. Thus, a decrease in immunoproteasome levels may lead to a breakdown of self-tolerance, resulting in an increase of CD8 + T cells directed towards melanocytes in predisposed individuals which could not be checked upon by the insufficient numbers and functionally deficient regulatory T cells (Tregs) in patients with vitiligo [58,59]. …”
Section: Discussionmentioning
confidence: 99%